SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KEPALA BAGIAN DISTRIBUSI PADA PDAM TIRTAULI PEMATANGSIANTAR DENGAN MENGGUNAKAN METODE SAW - Ahmad, Abdullah; Solikhun, Solikhun; Andani, Sundari Retno (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
The study, entitled "Supporting System for the Decision of the Head of Distribution Section at PDAM Tirtauli Pematangsiantar Using the SAW Method" aims to produce a Supportive System that is objective and systematic in determining the distribution heads who have the best qualifications. The research data is sourced from the relevant agencies in 2018. The data that is used as a reference for the requirements of the system requirements that are built is obtained from interviews with relevant agencies. From the interview, it was found that the problem of lack of objectivity and transparency of information in the process of determining the section head in any sector including the determination of the head of the distribution section is the absence of a standard or system used in determining the section head and only using manual selection method so that the determination of the section head is determined subjectively. In addition, the Candidates / alternatives recommended by PDAM Tirtauli themselves consist of 5 employees from a total employee population of 362 with the highest criteria and 5 criteria as the requirements for the assessment of the candidates for the head of the distribution department itself covering the criteria of responsibility (C1), achievement motivation (C2) , discipline (C3), communicative (C4), and working period (C5). This study uses the Simple Additive Weighting (SAW) method. With this system, agency leaders can produce a decision to choose the best distribution head more objectively.Keywords: Election of Distribution Section Head of PDAM Tirtauli Pematangsiantar, Decision Support System (SPK), Simple Additive Weighting (SAW)